Biophilic Design in Healthcare Centre - Vaishnavi; Deepti Pande Rana; Suparna Sircar (International Journal of Environmental Planning and Development Architecture, 2023)
The human affinity towards nature is innately genetic and has a strong correlation with human well- being. This innate affiliation towards nature has been coined as Biophilia which focuses on the growing need for human interaction with nature, nature-like elements, and the natural environment in and around the built form for improving human well-being. Biophilic design can also provide physical opportunities offered through its design considerations in the realization of the sustainable built form and environment. Biophilic design is crucial in creating a connection between nature and the built environment as the globe continues to become more urbanized. Biophilic design can relieve stress, encourage human creativity, and make people feel more at ease. It improves well-being and speeds up healing. The advantages of biophilic design have been proven in several contexts, including bettering the working environment, promoting learning in children, and enhancing health. This paper attempts to explore and comprehend the implications of biophilia and biophilic components in healthcare facility design to improve the quality of the environment as well as the health and well- being of the users, and how advantages can be obtained in terms of users' experiences as well as the improvement in the quality of the built environment.
Keywords: Biophilia; Biophilic Design; Built environment; Natural landscapes; hospitals